Efektivitas permainan sensorimotor dalam meningkatkan konsentrasi dan kebugaran jasmani di masa pandemi covid-19 - Nyoman Trisna Narta Dewi, Anak Ayu; Satria Nugraha, Made Hendra; Gita Karunia Saraswati, Ni Luh Putu (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2023)
Changes in the learning process during the COVID-19 pandemic have caused a decrease in the concentration of learning in children who are brought to offline learning. This study aims to know the effectiveness of sensorimotor games in improving the concentration and physical fitness of children aged 7 – 12 years. The research method is an experimental design with a randomized pre and post-test control group design with 42 samples divided into 2 groups: a control group and a treatment group. Sensorimotor games are given using the sensory path for 5 repetitions in each session with 12 meetings. The measuring instrument in this study was the digit symbol test to measure concentration levels and 5 measuring tools to measure physical fitness. The data analysis used to test the hypothesis is the paired sample t-test to find out differences in 1 data group and the independent t-test to compare data between groups. Based on the results of the independent t-test between the treatment and control groups after being given a sensorimotor game, the concentration value was p=0.001, coordination p=0.001, balance p=0.000, flexibility p=0.453, agility p=0.228, speed p=0.873. Sensory-motor games improve concentration, coordination, and balance in children aged 7-12 years in Denpasar. Sensorimotor games using sensory pathways can be applied to children who experience a decreased concentration in learning and are an alternative to physical exercise to improve coordination and balance.